The ANALISIS PRAKTIK PENJUALAN SKINCARE TANPA IZIN EDAR PADA MEDIA SOSIAL : PERSPEKTIF FIQIH MUAMALAH DAN UNDANG - UNDANG PERLINDUNGAN KONSUMEN - Achmad Amir Farros; Mohammad Hipni (Accounting Journal of Ibrahimy (AJI), 2025)
The rapid development of the beauty industry had led to an increase in the sale of skincare products through social media. However, many products were marketed without a distribution license, which had the potential to harm consumers. This study aimed to analyze the practice of selling skincare without a distribution permit on social media based on the perspective of Islamic Law and the Consumer Protection Law. The research method used is an empirical legal approach with data collection techniques through literature studies, interviews and analysis of related laws and regulations. The results showed that in the perspective of Islamic Law, the practice of selling skincare without a distribution permit is contrary to the principles of justice and benefit because it can endanger consumer health. Meanwhile, in the perspective of the Consumer Protection Law, the practice violates the provisions of Article 8 of Law Number 8 of 1999 which prohibits the circulation of goods that do not meet safety and health standards. Thus, stricter supervision from the government is needed as well as increased consumer awareness to be more selective in buying skincare products. This research was expected to contribute to the development of more effective regulations in addressing the circulation of illegal products on social media.